Frond Base Fracture and Dynamics of Palm Oil Inflorescence Applied With Different Nutrient Sources - Suprih Wijayani; Herry Wirianata; Sri Gunawan (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Frond base fracture is an increasingly common phenomenon in oil palm plantations caused by various stress factors. This study aimed to determine the incidence of frond base fracture in the plantation where different nutrient sources were applied (palm oil mill effluent, oil palm EFB, and organic fertilizers) in relation to the dynamics of oil palm inflorescence. The incidence of frond base fracture and the production of male and female inflorescences were observed in 30 sample trees for each nutrient source. Observations were made three times with an interval monthly. To reveal the research objectives, it used descriptive analysis. The results showed that the routine application of POME increased the susceptibility of oil palms to fractured fronds and the sex ratio was higher other than that of EFB; the lowest incidence was found in the palm that was given inorganic fertilizers. frond base fracture trees produced fewer female inflorescence, although the number of male ones did not differ between frond base fracture palm and healthy ones.